Design and Implementation of a Construction Budgeting Application for Residential Projects on Android Platform Using the Waterfall Method - Deddy Rudhistiar; Muhammad Hasan Wahyudi; Hadi Surya Wibawanto Sunarwadi; Amar Rizqi Afdholy; Thesa Adi Saputra Yusri (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2025)
Building a home is one of the most important and basic human needs. However, uncertainty around construction schedules and cost details often pose significant obstacles for individuals and families. The process can be overwhelming, especially for those with less experience in building homes. This is where information technology can play a vital role in streamlining the home-building process. By harnessing the power of technology, the building process can be simplified, providing greater transparency and convenience to users. To address these challenges, the Halo Rumah app was developed. The app helps users choose the right design and materials for their home construction. The app has an intuitive interface that allows users to explore a variety of home designs tailored to different preferences and choose materials that suit their needs and budget. Additionally, the app offers a range of advanced tools that help users estimate and calculate the costs of building a home, giving them a clear picture of their financial needs before starting the building process. By integrating these features, the Halo Rumah app ensures that users can make informed decisions, reduce uncertainty, and plan their dream home more effectively. Based on black box testing of 5 features tested on the Halo Rumah application, the research results show that the 5 features in the application can function according to the expected results.